2022
DOI: 10.1002/1348-9585.12314
|View full text |Cite
|
Sign up to set email alerts
|

The association between work-related physical and psychosocial factors and musculoskeletal disorders in healthcare workers: Moderating role of fear of movement

Abstract: Objectives Knowledge is lacking on the interaction between fear of movement (FOM) and work‐related physical and psychosocial factors in the development and persistence of musculoskeletal disorders (MSDs). Methods In this cross‐sectional study, 305 healthcare workers from several Belgian hospitals filled out a questionnaire including sociodemographic factors, work‐related factors (social support, autonomy at work, workload, and physical job demands), FOM, and MSDs for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
(180 reference statements)
0
3
0
Order By: Relevance
“…Recent studies show that many office workers are exposed to problems related to CANS. For example, the frequency of these complaints has been estimated at 42% to 83.5% for neck pain, 40% to 62.3% for shoulder pain, and 13.9% for wrist pain ( 3 , 12 ). Within Iran, studies have demonstrated a heightened susceptibility of office workers to musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that many office workers are exposed to problems related to CANS. For example, the frequency of these complaints has been estimated at 42% to 83.5% for neck pain, 40% to 62.3% for shoulder pain, and 13.9% for wrist pain ( 3 , 12 ). Within Iran, studies have demonstrated a heightened susceptibility of office workers to musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical risk factors include uncomfortable posture, carrying large items, and repetitive activities (Tang et al, 2022). Psychosocial risk factors include psychological suffering, insufficient social support, and limited decision-making authority (Keyaerts et al, 2022). Social factors include culture, beliefs, and cultural beliefs Keyaerts (2022), and individual characteristics consist of things like body mass index, age, gender, lifestyle, and living environment (Svensson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial risk factors include psychological suffering, insufficient social support, and limited decision-making authority (Keyaerts et al, 2022). Social factors include culture, beliefs, and cultural beliefs Keyaerts (2022), and individual characteristics consist of things like body mass index, age, gender, lifestyle, and living environment (Svensson et al, 2020). Given the influence of various risk factors on the incidence of MSDs, the implementation of prevention and control programs and measures requires the simultaneous identification and control of a series of risk factors (Tang et al, 2022) Some studies explain that Age, Length of work, Length of work, Gender, Workload, Repetition, Psychosocial factors, Work posture, Work climate, Stress, Body mass Index, Exercise frequency, History of muscle complaints, Education Anxiety, Fear, charity, company size, duration of work can be a risk factor for occurrence Muscoloskelatal Disorders (MSDs) (Shobur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Various workplace risk factors have been implicated in the occurrence of musculoskeletal pain among healthcare workers. These include ergonomic factors and physical job demands [6,7], long working hours and night shifts [8], psychosocial and emotional burdens of the profession [3] and perceptions about workplace support [7]. A recent study conducted in Egypt found the prevalence of musculoskeletal disorders among physicians to be as high as 74% [9].…”
Section: Introductionmentioning
confidence: 99%